Plan de negocios ecommerce para el estudio de una estrategia de diferenciación digital - Diaz Santillan, Julio Enrique (My University, 2020)
In this research work, the objective of designing an e-commerce business plan using comparative tables of tools and platforms is proposed in order to segment the most feasible ones that allow generating the digital differentiation strategy. Through the use of the analytical-synthetic method, it allows to analyze, decompose and study the business model to extract the digital differentiation strategy. They are presented on the most used social media platforms such as facebook, instagram and whatsaap, which allow each of their paid marketing tools to be differentiated according to the user's need, which will be for a period and a predetermined value. The costs of paid advertising are similar, but vary in modification of the estimated duration of the post that will have an expansion of hundreds to thousands of views. The use of platforms and tools focused on e-commerce allows the transformation of a physical store to a virtual one, generating electronic transactions.
En el presente trabajo de investigación se plantea el objetivo de diseñar un plan de negocios e-commerce mediante cuadros comparativos de herramientas y plataformas con la finalidad de segmentar las más factibles que permitan generar la estrategia de diferenciación digital. mediante el uso del método analítico-sintético permite analizar, descomponer y estudiar el modelo de negocios para extraer la estrategia de diferenciación digital. Se presentan en las plataformas de redes sociales más utilizadas como facebook, instagram y whatsaap, que permiten diferenciar cada una de sus herramientas de marketing de pago según la necesidad del usuario que será por un periodo y un valor predeterminado. Los costos de la publicidad pagada son similares, pero varían en modificación del tiempo estimado de duración del post que tendrá una expansión de cientos a miles de views. El uso de plataformas y herramientas enfocadas al e commerce permite la transformación de una tienda física a una virtual generando transacciones electrónicas.
Keywords: COMERCIO ELECTRÓNICO; BUSINESS TO CONSUMER; REDES SOCIALES; INNOVACIÓN